Who gets help for pre‐school communication problems? Data from a prospective community study. Issue 2 (22nd March 2013) - Skeat, J.; Wake, M.; Ukoumunne, O. C.; Eadie, P.; Bretherton, L.; Reilly, S.
Abstract Objective Pre‐school communication problems are common, with implications for school readiness and educational achievement. Help is available from a variety of community healthcare providers. This study examined the extent to which help is received, and the predictors of service receipt. Design and setting Prospective community study, in Melbourne, Victoria. Participants and method At age 4 years, we assessed the speech, receptive and expressive language and fluency of 1607 children and gave feedback to their parents. At age 5 years, 983 families provided data on service use for communication problems between and 4 and 5 years. We compared service use between participants with and without impairment, and used logistic regression to estimate the strength of association between potential predictors (gender, socio‐economic status, maternal education, English‐speaking background status, family history of speech and language problems and parent concern) and service use (binary outcome). Results Data were available for both communication status and service use for 753 children. Only 44.9% of the 196 children with communication impairment received help from a professional. Furthermore, 7% of the 557 that did not meet criteria for communication impairment nevertheless received help from a professional. Parent concern was the strongest predictor of service use (adjusted odds ratio = 9.0; 95% CI: 5.6–14.8). Conclusions Both over‐ and under‐servicing for communication problems were evident. This study shows that accessing help for communication problems requires more than simply informing parents about the problem and having services available; there is a need for systematic support to get the right children to services.